The Impact of Yogyakarta International Airport (YIA) Development on the Economy in the Special Region of Yogyakarta: Input-Output Analysis - Listikarini, Dian Irsalina; Harlan, Evan (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
One of the infrastructures built to enhance global relations in Yogyakarta is Yogyakarta International Airport (YIA), located in Kulon Progo Regency. The airport is also equipped with supporting infrastructure, namely Airport Train. The government hopes that the construction of YIA will have an impact on the economy, especially the DIY Province, both directly and indirectly. Thus, this study aims to identify the impact of the economic shock of the construction of YIA using the 2016 DIY Province 52 Industry Input-Output tables issued and updated by the Central Bureau of Statistics in May 2021. This study found that the multiplier effect on the economy is greater than economic shocks with the construction sector being the most affected sector with a value of IDR 12.8 trillion. It can be concluded that the construction of YIA and its supporting infrastructure brought a positive impact on the economy of DIY Province due to the increase in economic growth as well as the increase in GRDP and the economy of its society directly.